2020
DOI: 10.1016/j.bjae.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of sacrococcygeal pain

Abstract: Outline the underlying pathology causing coccydynia and sacroiliac joint pain. Discuss the diagnosis and management of coccydynia. Summarise the diagnosis and management of sacroiliac joint pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Their study revealed that ganglion impar helps in decreasing the neuropathic component of chronic coccydynia; which improves painless sitting in patients. 11 Yet, its reflections on quality of life is ambiguous. However, Savas et al conducted another comparative analysis on the treatment outcomes in using ganglion impar blockade and caudal epidural steroid injection to treat chronic coccygodynia among patients.…”
Section: Discussionmentioning
confidence: 99%
“…Their study revealed that ganglion impar helps in decreasing the neuropathic component of chronic coccydynia; which improves painless sitting in patients. 11 Yet, its reflections on quality of life is ambiguous. However, Savas et al conducted another comparative analysis on the treatment outcomes in using ganglion impar blockade and caudal epidural steroid injection to treat chronic coccygodynia among patients.…”
Section: Discussionmentioning
confidence: 99%
“…One study was conducted in New Zealand. Similarly, female sacrococcygeal vertebrae are short [ 3 ], which promotes coccydynia [ 71 , 72 ]. The word coccydynia was first developed in 1859 by Simpson and is also known as coccygodynia and tailbone pain [ 37 , 72 ].…”
Section: Discussionmentioning
confidence: 99%